Emblematic strategies in Pre-Raphaelite literature - McAlpine, Heather (Costerus, 2020)
"In this book, Heather McAlpine argues that emblematic strategies play a more central role in Pre-Raphaelite poetics than has been acknowledged, and that reading Pre-Raphaelite works with an awareness of these strategies permits a new understanding of the movement's engagements with ontology, religion, representation, and politics. The emblem is a discursive practice that promises to stabilize language in the face of doubt, making it especially interesting as a site of conflicting responses to Victorian crises of representation. Through analyses of works by the Pre-Raphaelite Brotherhood, Christina Rossetti, Dante Gabriel Rossetti, Gerard Manley Hopkins, A.C. Swinburne, and William Morris, Emblematic Strategies examines the Pre-Raphaelite movement's common goal of conveying "truth" while highlighting differences in its adherents' approaches to that task"--